Reality TV - Kavka, Misha (Edinburgh : Edinburgh University Press, 2012)
Is reality TV a coherent genre? This book addresses this question by examining the characteristics, contexts and breadth of reality TV through a history of its programming trends. Paying attention to stylistic connections as well as key concepts, this study breaks reality television down into three main'generations': the camcorder generation, the competition generation and the celebrity generation. Beginning with a consideration of the applicability of the term'genre' for this televisual hybrid, the book takes a transnational approach to investigating the forms and formats of reality TV framed by relevant popular and critical discourses.
Introduction: what is reality TV? -- Before reality TV: from Candid Camera to Family docs -- First-generation reality TV (1989-99): the camcorder era -- Second-generation reality TV (1999-2000): Surveillance and competition in Big Brother and Survivor -- The second generation comes of age (2001-5): challenge and transformation -- Third-generation reality TV (2002- ): economies of celebrity -- Legacies: the new MTV generation.
Includes bibliographical references (p. 183-194) and index.
Keywords: Reality television programs -- History and criticism